Precision Repetitive Transcranial Magnetic Stimulation Over the Left Parietal Cortex Improves Memory in Alzheimer’s Disease: A Randomized, Double-Blind, Sham-Controlled Study - Jia, Yanli; Xu, Luoyi; Yang, Kehua; Zhang, Yingchun; Lv, Xinghui; Zhu, Zhenwei; Chen, Zheli; Zhu, Yunlong; Wei, Lili; Li, Xia; Qian, Mincai; Shen, Yuedi; et al. (Frontiers in Aging Neuroscience, 2021)
Objective: We aim to study the effect of precision repetitive transcranial magnetic stimulation (rTMS) over the left parietal cortex on the memory and cognitive function in Alzheimer’s disease (AD). Methods: Based on the resting-state functional magnetic resonance imaging, the left parietal cortex site with the highest functional connectivity to the hippocampus was selected as the target of rTMS treatment. Sixty-nine AD patients were randomized to either rTMS or sham treatment (5 sessions/week for a total of 10 sessions). The Mini-Mental State Examination (MMSE), 12-Word Philadelphia Verbal Learning Test (PVLT), and Clinical Dementia Rating (CDR) were assessed at baseline and after the last session. Results: After two-week treatment, compared to patients in sham group, those in rTMS group scored significantly higher on PVLT total score and its Immediate recall subscale score. Moreover, in rTMS group, there were significant improvements after two-week treatment, which were manifested in MMSE total score, and its Time orientation and Recall subscale scores, as well as PVLT total score, and its Immediate recall and Short delay recall subscale scores. In sham group, PVLT total score was significantly improved. Conclusions: The target site of left parietal cortex can improve AD patients’ cognitive function, especially memory, providing a potential therapy.